Courseware development with animated pedagogical agents in learning system to improve learning motivation. Issue 3 (2nd April 2016) - Chin, Kai-Yi; Hong, Zeng-Wei; Huang, Yueh-Min; Shen, Wei-Wei; Lin, Jim-Min
Abstract : The addition of animated pedagogical agents (APAs) in computer-assisted learning (CAL) systems could successfully enhance students' learning motivation and engagement in learning activities. Conventionally, the APA incorporated multimedia materials are constructed through the cooperation of teachers and software programmers. However, the thinking and technical gap between two roles, a concept/content provider (teacher) and an implementer (software programmer), may lead to the concept distortion and loss in the final teaching material implementations. This often results in preventing a teacher from preparing his or her own APA-based multimedia learning systems. This study aims to develop a courseware to facilitate the CAL through the combination of the two roles into a single one and then teachers can use it freely by themselves. The courseware can help teachers to develop appropriate multimedia instructional materials incorporating APAs, which attracts students' attention and enhances their interest in learning. Furthermore, in this study two separate trial experiments were conducted to measure the teachers' satisfaction with the courseware and students' learning motivation after using APA-based multimedia learning systems. The results show that the participating teachers were satisfied with the courseware and would like to apply it in their instruction. Moreover, the participating students were strongly motivated by the customized APA-based multimedia learning systems. Therefore, the proposed courseware could give teachers a good opportunity to add pedagogical value to the curriculum, so that students' learning interest and motivation could be enhanced.